VIRTUAL TOURISM EXHIBITION ACTIVITY IN ENGLISH FOR TOURISM CLASS: STUDENTS’ PERSPECTIVES - Suprayogi Suprayogi; Budi Eko Pranoto (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2020)
As the need of the contextual learning for English for Tourism class increases, the new teaching methods with integration of technology need to be further explored. Recently, the common method used in the class usually focuses on monologue, lecture, video exploration and presentation, meanwhile, contextual simulation is rarely used and addressed. This study aims at observing the implementation of virtual tourism exhibition activity in English for Tourism class from the students’ perspectives. Qualitative descriptive study was employed by selecting 56 students of English Literature major in T university as research subject. A questionnaire focusing on the area of learning objective, technology literacy and interaction was used to collect the necessary data. The result shows that virtual tourism exhibition has given them a learning alternative during COVID-19 quarantine, some improvement in speaking has been made, and the degree of technology literacy to conduct virtual learning was found  to be satisfying. However, students still prefer having face-to-face activity to virtual meeting. Further, the interaction between students and lecturer is still covered despite of limited time and unstable internet connection. This study suggests that the analysis from the teacher perspective and quantitative calculation on students’ performance in exhibition simulation should be further explored.